DOPING A SILICON SINGLE CRYSTAL WITH TERBIUM THROUGH DIFFUSION. - Saidimov Ya.A.; Rumi R.F.; Umarov F.B. (Research Focus International Scientific Journal, 2024)
Using the diffusion method, monocrystalline samples of silicon doped with Thulium were prepared at 1250 degrees Celsius for 50 hours. The samples were found to have p-type conductivity after high-temperature annealing. After this process, the samples changed their type of conductivity from p-type to n-type.